Musical Instrument Classification using Audio Features and Convolutional Neural Network - Giri, Gst. Ayu Vida Mastrika; Radhitya, Made Leo (Politeknik Negeri Batam, 2024)
This research classifies acoustic instruments using Convolutional Neural Network (CNN). We utilize a dataset from Kaggle containing audio recordings of piano, violin, drums, and guitar. The training set consists of 700 guitar, percussion, violin, and 528 piano samples. The test set contains 80 samples of each instrument. Features such as Mel spectrograms, MFCCs, and other spectral and non-spectral characteristics are extracted using the Librosa package. Three feature sets